NSAID-Exacerbated Respiratory Disease (NERD): From Pathogenesis to Improved Care - Woo, Seong-Dae; Luu, Quoc Quang; Park, Hae-Sim (Frontiers in Pharmacology, 2020)
Nonsteroidal antiinflammatory drug (NSAID)-exacerbated respiratory disease (NERD) is characterized by moderate-to-severe asthma and a higher prevalence of chronic rhinosinusitis/nasal polyps, but is a highly heterogeneous disorder with various clinical manifestations. Two major pathogenic mechanisms are: (1) overproduction of cysteinyl leukotrienes with dysregulation of arachidonic acid metabolism and (2) increased type 2 eosinophilic inflammation affected by genetic mechanisms. Aspirin challenge is the gold standard to diagnose NERD, whereas reliable in vitro biomarkers have yet not been identified. Therapeutic approaches have been done on the basis of disease severity with the avoidance of culprit and cross-reacting NSAIDs, and when indicated, aspirin desensitization is an effective treatment option. Biologic approaches targeting Type 2 cytokines are emerging as potential therapeutic options. Here, we summarize the up-to-date evidence of pathophysiologic mechanisms and diagnosis/management approaches to the patients with NERD with its phenotypic classification.